Bilharzial vs non‐bilharzial related bladder cancer: pathological characteristics and value of cyclooxygenase‐2 expression - Youssef, Ramy; Kapur, Payal; Kabbani, Wareef; Shariat, Shahrokh F.; Mosbah, Ahmed; Abol‐Enein, Hassan; Ghoniem, Mohamed; Lotan, Yair (BJU international, 2011)
Study Type – Prognostic (case series)  Level of Evidence 4 What’s known on the subject? and What does the study add? Bilharziasis is the reason for the high incidence of bladder cancer in Egypt. Some of the clinico‐pathological characteristics of bilharzia‐associated bladder cancer has been published before. This paper adds insight about the biology of the disease. COX‐2 shows usefulness as a prognostic marker for bilharzia‐associated bladder cancer, which might open avenues for preventive and therapeutic strategies utilizing COX‐2 inhibitors in the management of bladder cancer arising on top of chronic inflammation. OBJECTIVE • To assess the expression pattern of cyclooxygenase‐2 (COX‐2) in bilharzial and non‐bilharzial related bladder cancer (BBC and NBBC) and its association with clinical outcome after radical cystectomy (RC). We also determined the clinico‐pathological differences between BBC and NBBC. PATIENTS AND METHODS • Immunohistochemical (IHC) staining for COX‐2 was performed on archival bladder specimens from 315 patients treated with RC between 1997 and 2003. • Patients were divided into 2 groups: Group 1 comprised 205 patients (65%) with BBC and group 2 comprised 110 patients (35%) with NBBC. • Clinico‐pathological differences were compared and altered IHC expression of COX‐2 was correlated with clinical outcome in both groups. RESULTS • The study included 315 patients (239 males and 76 females) with median age 54 y (range 31–79) and median follow up of 63.2 months after RC. • There was significant difference in histological types, tumor stage, grade, and architecture and COX‐2 alterations between both groups (P < 0.05). • BBC presented with lower grade, higher stage, and non‐papillary non‐urothelial carcinoma. COX‐2 overexpression was associated with pathological T stage (P= 0.01), grade (P < 0.001) and lymphovascular invasion (LVI) (P= 0.041). • COX‐2 expression was an independent predictor of disease recurrence (HR 1.9, CI 0.99–3.626 and P= 0.05) and cancer specific mortality (HR 2.8, CI 1.155–6.73 and P= 0.023) only in BBC but not in NBBC (HR 1.6, CI 0.598–4.364, P= 0.344 and HR 0.349, CI 0.076–1.595, P= 0.175, respectively). CONCLUSIONS • BBC differs pathologically and biologically from NBBC. BBCs present more frequently as low‐grade, high stage non‐papillary and non‐urothelial cancers. BBCs with COX‐2 alterations are associated with worse outcome after RC. • Our findings support the need for further evaluation of COX‐2 and inflammatory signaling pathways as well as COX‐2‐targeted prevention and therapies in BC.